Diesel/ biodiesel /silver thiocyanate nanoparticles/hydrogen peroxide blends as new fuel for enhancement of performance, combustion, and Emission characteristics of a diesel engine. (1st February 2021) - Elkelawy, Medhat; Etaiw, Safaa El-din H.; Alm-Eldin Bastawissi, Hagar; Ayad, Mohamed I.; Radwan, Ahmed Mohamed; Dawood, Mohamed M.
Abstract: In the present study, sunflower and soybean oil commixture with 50:50 V/V % had been used to produce biodiesel by using a homogeneously catalyzed transesterification. The influence of biodiesel blend, nano blended fuel, and nanoemulsion fuel blends on the combustion, performance, as well as emissions of DI diesel engine, had been examined in the laboratory at various engine loads and a steady speed of 1400 rpm. Volumetric proportions of fuel mixtures: D50B50N000 (50% diesel-50% biodiesel), D50B50N200 (D50B50 + 200 ppm silver thiocyanate AgSCN (SCP1 ∖ ), D50B50N200 + 2% hydrogen peroxide (H2 O2 ), and D50B50N200 + 4%H2 O2 were arranged to fuelling a one-cylinder engine. The exhaust emissions of the engine were compared at pure diesel fuel and biodiesel blend D50B50N000, which indicated a reduction in CO, UHC, and NOx emissions upon adding a 200-ppm of silver thiocyanate SCP1 ∖ as a nano additive. This reduction increased upon adding and increasing the volumetric percentage of H2 O2 where the D50B50N200 + 4% H2 O2 fuel blend has lower emission values. The results show that CO2 emissions for the investigated fuel blends were elevated than diesel fuel. The presence of nanosized AgSCN and H2 O2 enhanced the combustion process because of elevated nanoparticle surface/volume ratio and the occurrence of micro-explosion phenomena of the sprayed fuel particles, which increased the in-cylinder pressure and heat release rate (HRR). A noticeable decrease in brake specific fuel consumption (BSFC) was observed owing to the positive effect of using nano biodiesel blend and nanoemulsion fuels. A consequent increment in brake thermal efficiency (BTE) was indicated for nano biodiesel blend and nanoemulsion biodiesel blend fuels, where D50B50N200 + 4%H2 O2 has the highest BTE of 27.16% compared to all tested fuels. Exhaust gas temperature (EGT) values were evaluated and analyzed for all tested fuels. Highlights: AgSCN(SCP1 ∖ ) Nanoparticles/H2 O2 emulsion is used to enhance diesel engine operation. The improvement of DI-engine relies on the aid of nanoemulsion fuel additives. Engine exhausts emissions reduced by increasing the percentage of H2 O2 additives. The presence of AgSCN (SCP1 ∖ ) as nanosized with H2 O2 enhance the combustion process. NOx emission were dramatically reduced by adding the emulsion to the fuel blends.